Long-term Follow-up of Partial Thrombosis of the Superior Mesenteric Vein in a Cirrhotic Patient with Hepatocellular Carcinoma - Men-Shun Hsieh (Kaohsiung Journal of Medical Sciences, 2003)
Superior mesenteric venous thrombosis (SMVT) is an uncommon but potentially life-threatening disorder. We describe a cirrhotic patient with hepatocellular carcinoma who had partial SMVT for at least 28 months. Our experience may help in the management of such patients. The partial SMVT was not treated at the time of discovery because there was no evidence of bowel infarction. Moreover, the patient had a tendency to bleed severely and was in a poor condition. SMVT was followed using regular ultrasonography and the pattern of SMVT did not change significantly during the follow-up period. A symptom that may have been related to SMVT was abdominal colic pain after meals, which was sometimes followed by diarrhea and/or nausea and vomiting. There was no evidence of bowel ischemia or infarction during follow-up. Abdominal discomfort can be successfully treated using anticholinergic drugs with or without analgesia.